Epitheloid Hemangioendothelioma of the Palpebral Lobe of the Lacrimal Gland. (April 2013) - Kiratli, Hayyam; Tarlan, Berçin; Ruacan, Şevket
ABSTRACT Purpose: To describe a case of an epitheloid hemangioendothelioma which is a tumor of endothelial origin with borderline malignancy between hemangioma and angiosarcoma and which is very rare in the orbit. Methods: Clinical features, results of imaging and histopathological studies and postoperative clinical course of a 22-year-old female patient who presented with a gradual swelling of the left upper eyelid were reviewed. Results: Magnetic resonance imaging studies suggested a solid lesion with moderate contrast enhancement in the palpebral lobe of the lacrimal gland. A short course of systemic corticosteroid therapy failed to resolve the lesion. Excisional biopsy of the tumor yielded the diagnosis of epitheloid hemangioendothelioma of the lacrimal gland. The tumor was composed of nests of epitheloid cells, some forming CD31 positive intracytoplasmic vascular channels containing erythrocytes. CD34 and EMA were also positive and desmin, SMA, p63, S100, Factor VIII and HHV-8 were negative on immunohistochemical studies. During 44 months of follow-up, there has been no recurrence or systemic metastasis. Conclusion: Epitheloid hemangioendothelioma can occur in the palpebral lobe of the lacrimal gland as a hard, painless, immobile mass. Simple excisional biopsy of the tumor, assumed to have an intermediate malignancy grade, without further local or systemic therapy provided a disease-free 3-year survival.